PGcloser: Fast Parallel Gap-Closing Tool Using Long-Reads or Contigs to Fill Gaps in Genomes. (April 2020) - Lu, Peng; Jin, Jingjing; Li, Zefeng; Xu, Yalong; Hu, Dasha; Liu, Jiajun; Cao, Peijian
Assembled draft genomes usually contain many gaps because of the length limit of next-generation sequencing. Although many gap-closing tools have been developed, most of them still attempt to fill gaps on the basis of next-generation sequencing reads (always < 200 bp). Hence, the gap-filling effect is inferior. Several tools that use long-reads to close gaps have recently been created. However, they require extensive runtimes, which may not be suitable for large genomes. We describe a gap-closing tool called PGcloser, which supports parallel mode and adopts long-reads/contigs to fill gaps in genome sequences. Three tests show that PGcloser is faster than other tools but exhibits similar accuracy. PGcloser is free open-source software that is available athttp://software.tobaccodb.org/software/pgcloser .